A prospective study of 1393 cases of adenotonsillectomy in a tertiary referral centre. A curious alternate Year surge in incidence. - RANJANA KUMARI; RAVI K; MOGIT GUPTA Y (International Journal of Pharma and Bio Sciences, 2017)
The aim of this study is to know the pattern of the proportions of patients who underwent Adenotonsillectomy or Tonsillectomy in a tertiary referral hospital in Chennai city during 2006 – 2013.This is a prospective study conducted in a tertiary referral center during 2006 - 2013. All the patients who came for Adenoidectomy and/or Tonsillectomy during this period were included in the study. The various symptoms associated with adenoidectomy were studied. Statistical Package for Social Sciences (SPSS) version 22.0 is used to analyze the data. The total number patients underwent for Adenoidectomy and/or Tonsillectomy were 1393. Among the patients 58.7% were females, 66.1% were under the age of 14 years. Almost all (99.5%) experienced throat pain. Nasal obstruction was observed in 83.2% of patients. Snoring was noticed in 54.0% of patients. Age group, Nasal discharge, Nasal obstruction, Snoring, and Ear discharge were strongly associated with Adenoidectomy (P<0.001). A curious phenomenon was observed i.e. every alternate year there was a peak observed in the incidence of Adenoidectomy. A surge was found in the incidence of Adenoidectomy every alternate year. This requires further studies to find out whether it is related to climatic conditions or virulence of the causative organism. Such studies may give us insight into unknown causal factors and may be instrumental in instituting preventive and therapeutic measures.